(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aims to uncover the extent of interest in artificial intelligence applications, represented by (expert systems, customer profiling, chatbots, smart branches, fraud prevention, and credit risk management), within the surveyed Iraqi private commercial banks and their relationship to achieving the strategic position of these banks. The dimensions of strategic positioning include (shaping expectations, building social networks, and learning processes). The research was conducted in several banks, namely (Al-Ahly Iraqi Bank,Gulf Commercial Bank for Investment, Al-Mansour Investment Bank, Ashur International Investment Bank) The study adopted a descriptive-analytical approach, using a questionnaire distributed to a sample of 110 officials out of a total population of 125, covering senior, middle, and executive management levels. The statistical program (SPSS) was employed to calculate (weighted arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient, and t-test). The study concluded with key findings, most notably the existence of a strong and positive correlation between artificial intelligence applications and strategic positioning.